7. EVALUATION OF INPATIENT OBSTETRIC SERVICE QUALITY AT THE DEPARTMENT OF OBSTETRICS AND GYNECOLOGY, PHUONG DONG GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: describe the perceptions of inpatients about the quality of services at the Department of Obstetrics and Gynecology, Phuong Dong General Hospital in 2024.Methods: This cross-sectional descriptive study, employing both qualitative and quantitative methods, was conducted on 223 obstetric inpatients from March 2024 to September 2024.Results: 91.0% of the inpatients evaluated the service quality as satisfactory. The satisfaction rates for specific aspects were as follows: 96.0% for reliability, 96.9% for responsiveness, 99.1% for assurance, 95.5% for empathy, and 97.3% for tangibility.Conclusion: The high level of satisfaction with obstetric service quality suggests that further efforts are needed to enhance and sustain the quality of services in the future.
Keywords: Evaluation; Service quality; SERVPERF; Obstetrics